Volunteerism and elderly. - Dávila de León, Mª Celeste; Díaz-Morales, Juan Francisco (Anales de Psicología / Annals of Psychology, 2009)
The purpose of this paper is to carry out a revision of the stud-ies about volunteerism and elderly. This revision is organized in three subject matters: factors related with volunteering, relationship between volunteerism and employment/retirement, and benefits of volunteering. Finally, several strategies to improve the management of elderly volunteers are presented.